Synthesized Magnetic Manganese Ferrite Nanoparticles on Activated Carbon for Sulfamethoxazole Removal. Issue 9 (10th March 2014) - Wan, Junli; Deng, Huiping; Shi, Jun; Zhou, Li; Su, Tong
<x xml:space="preserve">Abstract</x> The presence of pharmaceutical compounds in water has adverse environmental and health impacts. The main objective of the current research are to investigate the removal efficiency of sulfamethoxazole (SMX) from aqueous solution by using magnetic manganese ferrite nanoparticles synthesized on powdered activated carbon (PAC). Magnetic activated carbon composites (MACC) were prepared by using chemical co‐precipitation at different temperature values ranging from 298 to 423 K. The obtained samples were characterized by contemporary characterization instrumental methods of analysis, and their SMX removal capabilities were evaluated. Results revealed that the procedure successfully created magnetic nanoparticles on PAC at temperatures of 298–423 K, and the anchored MnFe2O4/MnO2 manifested more crystalline forms at 423 K. As a result, MACC prepared at 423 K showed the highest magnetic and sorption capacities among three obtained samples. The SMX maximal adsorption capacity of MACC(423K) was 159 mg/g at pH 7, and the SMX adsorption remained stable at pH 3–7. The effect of common ions and humic acids on SMX adsorption indicates a high selectivity of MACC(423K) for SMX. Furthermore, MACC(423K) achieved much higher regeneration efficiency by H2O2 than that of virgin PAC, due to the presence of MnFe2O4/MnO2.